(untitled) (Annual of the Faculty of Philosophy in Skopje, 2025)
The Multicultural Workshops program was launched with an intention to enable students from different ethnic backgrounds to interact with each other through collaborative joint activities designed to provide conditions for learning from each other about each other’s culture. This paper presents the results from a quantitative pre- and post- intervention study carried out in two turns in one ethically mixed primary school where Roma students attend classes in Macedonian as a language of instruction. The participants were 58 ethnic Macedonian and 63 ethnic Albanian students from four age groups who took part in 12-15 Multicultural Workshops that included Roma students. In order to assess the effects of the exposure to the workshops on their perception of Roma, all participants were given a custom- designed instrument to identify the degree of social distance, trust and stereotypes towards them, as well as group anxiety and willingness for positive action. Taking into account the results that show differences in the participants’ perception of Roma and in their readiness to interact with them before and after the program, the paper concludes that, under defined conditions, this approach could be considered as an example of a good practice in integrating Roma students in primary education.